Phosphopenic form of osteomalacia in a patient with FGF23 producing tumor - A. S. Pushkareva; E. E. Bibik; A. K. Eremkina; M. V. Degtyarev; N. G. Mokrysheva (Научно-практическая ревматология, 2022)
Oncogenic osteomalacia is an orphan disease caused by the overproduction of fibroblast growth factor 23 (FGF23) in tumors, which leads to impaired bone matrix mineralization. Typical laboratory changes are hypophosphatemia, increased alkaline phosphatase, hyperphosphaturia, and decreased tubular phosphate reabsorption index. Surgery is the treatment of choice to eliminate an excessive production of FGF23. If surgical intervention is ineffective or impossible, preparations of phosphorus, calcium, vitamin D are prescribed. We present a clinical case of the stage-bystage diagnosis and treatment of the patient with chronic pain syndrome in the bones and multiple fractures.